Elongated styloid process: Is it a pathologic condition? - Najmeh Anbiaee; Abbas Javadzadeh (Wolters Kluwer Medknow Publications, 2011)
Objectives: The aims of this study were to evaluate the length, morphology, and calcification patterns of the elongated stylohyoid process (ESP) on panoramic radiographs and to investigate the symptoms related to it. We then addressed the question: Is ESP a pathologic condition or a physiologic phenomenon? Materials and Methods: In this study, 207 stylohyoid complexes were evaluated based on length, radiographic appearance, and calcification pattern on panoramic radiographs. Similar to previous studies, we considered 30 mm as a threshold for elongation of the process. Complexes were classified into two groups based on length: ESP (greater than or equal to 30 mm) and normal (less than 30 mm). Clinical symptoms were evaluated by using a questionnaire and clinical examination. Data were analyzed by the Kolmogorov-Smilonov test, Mann-Whitney U test, and Spearman correlation. Results: The average length of the stylohyoid complex was 31.7 mm. The median was 30.0 mm and corresponded to the threshold for the ESP. The Spearman correlation between the length of the complex and age was 0.323 (P=0.0001). "Continuous" and "calcified outline" were the most frequent morphology and calcification pattern, respectively, for both groups. Clinical symptoms related to ESP were not detected. Conclusion: Classification of the stylohyoid complexes based on apparent length on panoramic radiographs in elongated and normal types appears to be incorrect. Considering that the radiographic appearance of the ESP and normal groups was similar and pathologic symptoms were not detected and that there was a relationship between age and length of the complex, elongation of this complex can be considered as a physiologic phenomenon.